1986
DOI: 10.1136/jnnp.49.9.1030
|View full text |Cite
|
Sign up to set email alerts
|

Limb apraxia in patients with damage confined to the left basal ganglia and thalamus.

Abstract: SUMMARY Limb apraxia was investigated with standardised tests in 14 patients whose CT scan provided evidence of a vascular lesion confined to the left basal ganglia, or the thalamus, or both, and not involving the cortex or adjacent white matter. Five patients were severely impaired in imitating movements and pantomiming object use. Four of them also performed poorly when tested with real objects. In two patients the lesion was primarily thalamic and in three the lesion was primarily in the lenticular nucleus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 15 publications
1
23
0
Order By: Relevance
“…Thus, imitation of finger gestures is through activity of the frontal and parietal regions, but imitation of hand gestures seems to depend mainly on the temporoparietal regions. Moreover, some brain lesion studies also suggest involvement of the basal ganglia in the process of imitation of finger gestures 5 6 14. These findings suggest that imitation of finger gestures depends on a larger scale brain network including the frontal and parietal cortices, and the basal ganglia, compared to the imitation of hand gestures.…”
Section: Discussionmentioning
confidence: 87%
“…Thus, imitation of finger gestures is through activity of the frontal and parietal regions, but imitation of hand gestures seems to depend mainly on the temporoparietal regions. Moreover, some brain lesion studies also suggest involvement of the basal ganglia in the process of imitation of finger gestures 5 6 14. These findings suggest that imitation of finger gestures depends on a larger scale brain network including the frontal and parietal cortices, and the basal ganglia, compared to the imitation of hand gestures.…”
Section: Discussionmentioning
confidence: 87%
“…Individual scores are age and education adjusted. The cut off point (53) corresponds to the worst score found in a group of 187 controls 79 and represents the 95% outer tolerance limit of the normal population.…”
Section: Imitation Of Intransitive Gesturesmentioning
confidence: 99%
“…Specifically, results on lesion correlates of impairments in action, pantomime and gesture comprehension deficits are few, and not entirely consistent. Heilman and colleagues have reported that apraxic patients with posterior lesions have more trouble in comprehending the meaning of pantomimes (Heilman, Rothi, & Valenstein, 1982;Rothi, Heilman, & Watson, 1985) and have suggested that posterior parietal regions of the cortex may mediate the production and comprehension of purposeful movements (see also De Renzi, Faglioni, Scarpa, & Crisi, 1986;Kertesz, Ferro & Shewan, 1984). On the other hand, Ferro, Martins, Mariano, and Castro Caldas (1983) reported that while gesture recognition impairments were most commonly associated with parietal lesions in chronic stages of brain damage, in acute stages it was the patients with left frontal and basal ganglia damage who showed deficiencies, but unfortunately this study had a rather small sample size.…”
Section: Introductionmentioning
confidence: 99%